Strategic Interactions in Environmental Regulation: Evidence From Spatial Effects Across Chinese Cities - Zhang, Hua; Xu, Tiantian; Zhang, Yun; Zhou, Xiaoxiao (Frontiers in Environmental Science, 2022)
Abstract: Developing countries are notorious for their enforcement gap in environmental regulation. Despite policymakers and scholars focusing on this phenomenon in China, there is little literature to explore the cause for its prevalence. This paper aims to explain this occurrence from the perspective of strategic interactions among the local governments in China based on the yardstick competition theory. Employing spatial panel data models, we use a panel dataset of Chinese cities to investigate strategic interactions in environmental regulation and identify their possible sources. The results depict a confirmative picture of strategic interactions in environmental regulation among Chinese cities, suggesting that the cities tend to imitate their neighbors and implement looser environmental regulation in response to the decreasing stringency in neighbouring cities. This transmission effect demonstrates the prevalence of incomplete implementation of environmental regulation. Moreover, the imitative actions vary across Chinese cities, as they are observed in eastern and western cities but not in central cities. In addition, the imitative actions are significantly weaker when environmental governance gains a higher degree of salience, indicating that green performance appraisals reduce strategic interactions among local governments. Finally, strategic interactions are found to originate from the fiscal decentralization system, and are strengthened by the turnover of the municipal party secretary or a younger one.